Proceedings of the 15th International Conference on Environmental Degradation of Materials in Nuclear Power Systems - Water Reactors - Ilevbare, Gabriell; Busby, Jeremy; Andersen, Peter (The Minerals, Metals & Materials Series,, 2016)
This 15th Edition of the International Conference on Materials Degradation in Light Water Reactors focuses on subject areas critical to the safe and efficient running of nuclear reactor systems through the exchange and discussion of reseach results as well as field operating and management experience.